Maine organic dairy producers’ receptiveness to seaweed supplementation and effect of Chondrus crispus on enteric methane emissions in lactating cows - Reyes, Diana C.; Meredith, Jennifer; Puro, Leah; Berry, Katherine; Kersbergen, Richard; Soder, Kathy J.; Quigley, Charlotte; Donihue, Michael; Cox, Dorn; Price, Nichole N.; Brito, Andre F. (Frontiers in Veterinary Science, 2023)
There is interest in utilizing seaweed in ruminant diets for mitigating enteric methane (CH4) emissions while improving animal health. Chondrus crispus is a red seaweed that grows in the Gulf of Maine (USA) and has shown to suppress CH4 production in vitro. Organic dairy producers in Maine are currently feeding seaweed due to herd health promoting benefits. However, large-scale adoption depends on several factors, including validation from pilot studies. Therefore, a survey was developed to identify barriers and drivers towards the adoption of CH4-reducing algal-based feeds. All survey respondents were familiar with seaweed, and 34% were already users. Producers willing to pay 0.64 USD/cow/d on average for a CH4-reducing algal-based feed, stated the need for co-benefits (cattle health and performance) as a requirement for adoption. Concurrently, a RCBD study was conducted to investigate the effect of C. crispus on enteric CH4 emissions and milk production in a typical Maine organic dairy farm. Twenty-two organically certified cows averaging 29 ± 6.8 kg of milk/d and 150 ± 69 days in milk, were blocked and randomly assigned to a control diet without C. crispus (0CC), or with 6% [dry matter (DM) basis] C. crispus (6CC). Samples were collected on the last week of the 2-wk covariate period, and wk 3, 5, 8, and 10 after initiation of treatments. Gaseous emissions were measured using a GreenFeed unit. Data were analyzed using the MIXED procedure of SAS with repeated measures. Feeding 6CC decreased enteric CH4 production by 13.9% compared with 0CC (401 vs. 466 g/d).Further, milk yield (mean = 27.1 kg/d), CH4 intensity (mean = 15.2 g of CH4/kg of energy corrected milk), and concentrations (mean = 3.84 and 3.10%, respectively) and yields (mean = 1.06 and 0.86 kg/d, respectively) of milk fat and true protein were not affected by treatments. In summary, producer receptiveness to CH4-reducing algal-based feeds will not only depend on purchase price, but also on co-benefits and simplicity of integration into existing feed practices. Likewise, feeding C. crispus at 6% of the diet DM decreased CH4 production in dairy cows by 13.9% without negative effects on milk yield and composition.